2019
DOI: 10.1136/bcr-2018-226450
|View full text |Cite
|
Sign up to set email alerts
|

Transverse colon duplication with chronic constipation in adult

Abstract: Gastrointestinal duplications are extremely rare congenital abnormalities having definite difficulties to be diagnosed preoperatively. Most of them are presented at the oesophagus and ileum and only involve colon from 4% to 18%. We illustrate a case report of an 18-year-old female patient with transverse colon duplication. There were symptom manifestations such as chronic constipation with flatulence accompanied with abdominal pain. We demonstrate this case report due to non-specific clinical presentation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…There is a lack of unified diagnostic and treatment criteria for transverse colonic repetitive malformations. 12 cases were diagnosed using abdominal multirow CT ( 12 , 13 , 15 18 , 20 24 , 26 ), 8 cases using digitized barium enema colography ( 13 , 14 , 17 – 19 , 22 , 23 , 25 ), and colonoscopy in 4 cases ( 19 , 20 , 25 , 26 ), 8 cases using US ( 13 – 16 , 18 , 20 22 ) and 2 cases using plain X-ray ( 16 , 18 ). Because the symptoms of repeat transverse colon malformations in adults are mostly nonspecific, clinical diagnosis is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of unified diagnostic and treatment criteria for transverse colonic repetitive malformations. 12 cases were diagnosed using abdominal multirow CT ( 12 , 13 , 15 18 , 20 24 , 26 ), 8 cases using digitized barium enema colography ( 13 , 14 , 17 – 19 , 22 , 23 , 25 ), and colonoscopy in 4 cases ( 19 , 20 , 25 , 26 ), 8 cases using US ( 13 – 16 , 18 , 20 22 ) and 2 cases using plain X-ray ( 16 , 18 ). Because the symptoms of repeat transverse colon malformations in adults are mostly nonspecific, clinical diagnosis is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The manifestations of colonic duplication are non-specific, including abdominal mass, chronic constipation and abdominal pain, an acute abdomen, obstruction, perforation, and malignancy[ 4 - 6 , 13 , 14 ]. Our patient was disturbed by chronic abdominal pain and constipation since she was a child.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional treatment of alimentary duplication is surgical resection of both the duplicated and normal colon with an end-to-end anastomosis[ 24 , 25 ]. Most surgeons advocate that symptomatic patients should undergo elective surgery following accurate diagnosis[ 3 , 4 , 20 , 26 ]. It has been reported that symptomatic patients are treated successfully by surgery[ 8 , 16 , 19 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, colonic duplication is unusual, accounting for approximately 6%–7% of cases. To the best of our knowledge, there are no previous reports or research on cases involving a body fistula combined with a pelvic malformation[ 3 , 4 ]. This disease usually manifests as abdominal pain, distension, hematochezia, constipation, obstruction, perforation, and even intestinal twisting.…”
Section: Introductionmentioning
confidence: 99%